'Elimination signals' in healthy, NON toilet trained children aged 0–4 years: A systematic review. Issue 3 (June 2020) - Vermandel, Alexandra; Van Hall, Guido; Van der Cruyssen, Kelly; Van Aggelpoel, Tinne; Neels, Hedwig; De Win, Gunter; De Wachter, Stefan
Summary: Objective: An early start of toilet training, which is related to a younger age of acquiring full bladder control, can generate important health advantages. Children display different 'elimination signals' related to voiding or defaecation. The aim of this systematic review is to map these 'elimination signals' in young, healthy children aged 0–4 years. Method: The systematic literature search was performed in two databases and was conducted using the preferred reporting items for systematic reviews and meta-analyses (PRISMA statement). Results: Two main distinctions in elimination signals were made. The first could be classified as visual, auditory and tactile, most frequently involving a change in facial expression, often combined with body movements and verbal expressions such as a short cry or grunting. Secondly significant changes in heart rate, respiratory frequency or EEG frequency could be defined as 'clinically assessed elimination signals'. Conclusion: Different 'elimination signals' could be detected in healthy children while voiding or defaecating and should be observed when initiating toilet training. Detection of noticeable visual, auditory and tactile signals will facilitate and shorten this process.